2022
DOI: 10.1111/ene.15451
|View full text |Cite
|
Sign up to set email alerts
|

Detection of changes in synaptic density in amyotrophic lateral sclerosis patients using 18F‐SynVesT‐1 positron emission tomography

Abstract: Background and purpose: Synaptic loss is well established as the major correlate of characteristic and consistent pathology in amyotrophic lateral sclerosis (ALS). We aimed to assess the possible discriminant diagnostic value of 18 F-SynVesT-1 positron emission tomography (PET) as a marker of ALS pathology and investigate whether specific synaptic density signatures are present in ALS with different subtypes.Methods: Twenty-one patients with ALS and 25 healthy controls (HCs) were recruited.All participants und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…18 As an 18 F-labeled difluoro-analog of UCB-J, 18 F-SynVesT-1 has good properties similar to 11 C-UCB-J, which include high brain uptake, fast and reversible kinetics, and high specific binding. 19 It has been used in several neurological diseases, including amyotrophic lateral sclerosis 20 and focal cortical dysplasia type II. 21 In recent SV2A PET studies, Mecca et al found SV2A binding was widely reduced in medial temporal and neocortical brain regions in early AD compared to cognitively normal (CN) participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 As an 18 F-labeled difluoro-analog of UCB-J, 18 F-SynVesT-1 has good properties similar to 11 C-UCB-J, which include high brain uptake, fast and reversible kinetics, and high specific binding. 19 It has been used in several neurological diseases, including amyotrophic lateral sclerosis 20 and focal cortical dysplasia type II. 21 In recent SV2A PET studies, Mecca et al found SV2A binding was widely reduced in medial temporal and neocortical brain regions in early AD compared to cognitively normal (CN) participants.…”
Section: Introductionmentioning
confidence: 99%
“…18 As an 18 F-labeled difluoro-analog of UCB-J, 18 F-SynVesT-1 has good properties similar to 11 C-UCB-J, which include high brain uptake, fast and reversible kinetics, and high specific binding. 19 It has been used in several neurological diseases, including amyotrophic lateral sclerosis 20 and focal cortical dysplasia type II. 21…”
Section: Introductionmentioning
confidence: 99%
“…A recent synaptic PET study using 18F-SynVesT-1 on 21 amyotrophic lateral sclerosis (ALS) patients and 26 heatlhy controls from China ( Tang et al, 2022 ) revealed lower uptake in the ALS group compared to controls in specific brain regions including the right temporal lobe, bilateral inferior frontal gyrus, anterior cingulate, and hippocampus–insula area. This study also observed reduced uptake in the bilateral superior temporal gyrus, hippocampus–insula, anterior cingulate, and left inferior frontal gyrus in ALS patients with cognitive impairment versus controls.…”
Section: Sv2a Pet In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Similarly, studies in Parkinson's, have used this technique to confirm synaptic loss in the substantia nigra, red nucleus and locus coeruleus, the main affected areas in PD (Matuskey et al, 2020) as well as to study overall cerebral synaptic density in primary tauopathies (Holland et al, 2022). In ALS, 18 F-SynVesT-1 PET (another SV2 radiomarker) was used to assess synaptic density changes in different areas of the brain (Tang et al, 2022) and importantly, the results closely aligned with previous post-mortem data (Henstridge et al, 2018). Moreover, SV2A PET has also been used in frontotemporal dementia (FTD), which is thought to exist on a disease spectrum with ALS, to study synaptic density changes in patients with behavioral variant FTD (Malpetti et al, 2023), and in carriers of a repeat expansion in the chromosome 9 open reading frame 72 (C9ORF72) gene, which has been linked to both ALS and FTD (Malpetti et al, 2021).…”
Section: In Vivo Study Of Human Synapsesmentioning
confidence: 99%